Men's definitions of masculinity and male power - King, Eric V., author; Canetto, Silvia, advisor; Chavez, Ernest L., advisor; Banning, James H., committee member; James, Keith, committee member (Colorado State University. Libraries, 2000)
Many authors have stated that traditional masculinity is about power: the power of men over women and the power of some men over other men (Kimmel & Kaufman, 1995). It has also been asserted that any analysis of masculinity must examine its power aspects. While the last 20 years have seen a growth in the empirical study of masculinity, power issues inherent in traditional masculinity have been left unexamined. Additionally, diversity has been a recurring focus of theoretical studies of masculinity. Authors have argued that there are many forms, meanings, and views of masculinity (Brod, 1987: Connell, 1995). Yet, until recently, the theory of multiple masculinities coexisting within a society has been largely ignored in empirical studies. This study explored the relationship between men's definitions of masculinity and their perceptions of male power, and attempted to validate the theory of differing masculinities. The results from this study indicated there was a relationship between masculinity and perceptions of male power. This study also found evidence to support the theory of multiple masculinities. The findings from this study also indicated that men with different views on masculinity tended to differ on their views of male power. The implications of these findings are also discussed.
Keywords: social psychology